STRATEGI PENGEMBANGAN EKSPOR LADA INDONESIA DALAM PERDAGANGAN INTERNASIONAL - Ahmad Fatih Fairuz Zabadi; Sintya Amilia Fernanda; Elvira Dinda Kurniasari; Dewa Sukma Jagat Samudra; Alfan Danu Saputra; Arga Christian Sitohang (widya balina, 2025)
This study discusses the conditions, challenges, and strategies for developing Indonesian pepper exports in the context of international trade. Although Indonesia still has a comparative advantage as indicated by a positive RSCA value, export performance has continued to decline since 2019. Various internal factors such as inconsistent quality, limited post-harvest technology, and low cultivation productivity are the main causes of weakened competitiveness. On the other hand, competing countries such as Vietnam and India have succeeded in improving the quality and efficiency of their supply chains through technological modernization and the application of consistent quality standards. Through a literature review, this study found that strengthening the implementation of GAP and GHP, increasing farmer capacity, modernizing post-harvest technology, and developing product downstreaming are key strategies for improving the competitiveness of Indonesian pepper exports. The implementation of these strategies is expected to increase added value, improve Indonesia's position in the global value chain, and support the sustainability of pepper exports in the future.